Online Measurement Method for Circuit Breaker Mechanical–Time Characteristics Based on Transient Voltage and Current Signal Feature Extraction - Liting Weng; Jianhua Xia; Zhaochuang Zhang; Jingang Wang; Lin Chen; Yingbo Zi; Lingyi Ma; Xingyu Zhang; Fan Zhang; Pengcheng Zhao (Energies)
The good mechanical characteristics of circuit breakers are essential to ensuring their safe and stable operation. The characteristic signals at the points of initial opening and closing contain abundant information about the mechanical–time characteristics of the circuit breaker. Existing online measurement methods for circuit breaker mechanical–time characteristics typically rely on monitoring the secondary current signals of the opening and closing coils, or the signals such as vibration, pressure, and angular displacement that are generated during the opening and closing of moving and stationary contacts. Unlike these conventional approaches, this paper proposes an online measurement method for circuit breaker mechanical–time characteristics based on feature extraction from transient voltage and current signals in the primary circuit. By extracting features from the transient voltage and current signals in the primary circuit, this method obtains mechanical–time characteristics such as the points of initial opening and closing. This method is convenient and stable, enabling the online detection of the mechanical characteristics of the circuit breaker. Finally, a comparison and analysis of the online measurement results with the offline measurement results were conducted. The analysis shows that the calculation error of the opening and closing times is within 0.2 ms. This online detection method has a high measurement accuracy and provides a new approach for the online measurement of the mechanical characteristics of circuit breakers.